Experimental and Theoretical Analysis on the Dynamic Characteristics of Fused Filament Fabrication Plates - Shijie Jiang; Ming Zhan; Mingyu Sun; Weibing Dai; Chunyu Zhao (Shock and Vibration)
With the increasingly wide application of fused filament fabrication (FFF) technique, the built products are inevitably exposed to dynamic mechanical loading and vibration. However, there has been no systematic study in the literature on understanding and characterization of dynamic mechanical performance for FFF products. In this paper, the dynamic characteristics of FFF plates are quantified, with the effect of different extrusion width taken into account. A dynamic model of the built plate with cantilever boundary conditions is established, and the inherent characteristics are predicted. Modal tests are then performed on these samples to obtain the measured data. Through the comparison between predictions and measurements, the theoretical model is validated. Different extrusion width makes the material properties of the plates different, resulting in different dynamic characteristics. The scanning electron microscopy (SEM) analysis on the samples confirms that the dynamic characteristic is deteriorated as the extrusion width decreases. This present work provides theoretical basis and technical support for further research in improving the dynamic performance of FFF products and helps extend the applications of this technique.